From Administrative Correction to Criminal Prosecution: An Escalation Model for JKN Claim Fraud in Indonesia - Risqilah; Iin Karita Sakharina; Abdul Razak; Anggreany Arief; Anton Smirnov (PT. Islamic Research Publiser, 2026)
Indonesia’s National Health Insurance (JKN) reflects the constitutional commitment of the Indonesian welfare state to guarantee the right to health. Nevertheless, the program’s sustainability faces growing fiscal pressures, particularly due to healthcare fraud and abuses of authority in hospital-level fund management. This study aims to examine the available legal enforcement mechanisms for addressing abuses of authority in JKN governance and to formulate an ideal regulatory and enforcement design capable of strengthening accountability while safeguarding the sustainability of the health insurance system. This research employs a normative–empirical legal method. Normative analysis is conducted through a systematic and purposive interpretation of statutory regulations, judicial decisions, and relevant legal doctrines concerning health financing, administrative law, and anti-corruption law. Empirical data are obtained from a hospital-level case study and institutional observations to identify patterns of deviation, institutional roles, and coordination gaps among enforcement agencies. The findings reveal that enforcement currently operates through three principal pathways: administrative enforcement, criminal enforcement, and preventive governance mechanisms. Administrative enforcement includes sanctions by BPJS Kesehatan, audits by the Financial and Development Supervisory Agency (BPKP), and litigation before the Administrative Court (PTUN). Criminal enforcement is pursued through corruption proceedings before the Corruption Court (Tipikor) by the Prosecutor’s Office or the Corruption Eradication Commission (KPK), while preventive enforcement focuses on governance strengthening, digital monitoring, and compliance education. However, overlapping institutional mandates, weak inter-agency coordination, and the blurred distinction between administrative misconduct and criminal corruption significantly hinder effective enforcement. This study proposes an integrated, risk-based enforcement ladder that combines preventive, corrective, and repressive measures in proportion to risk. The article contributes theoretically by offering a clearer demarcation framework for administrative and criminal liability in healthcare fund governance, and practically by providing a tiered enforcement model to improve healthcare fraud control and preserve the long-term sustainability of JKN.